Географічна оцінка сучасного стану використання забудованих земель території Полісся (на прикладі Волинської області) - Тарасюк, Ніна Адамівна; Ничая, Олександра; Tarasiuk, Nina A.; Nychaia, Oleksandra (Тернопільський національний педагогічний університету імені Володимира Гнатюка, 2015)
У статті представлено результати оцінки особливостей сучасного використання забудованих земель для території Полісся Волинської області. В результаті аналізу структури земельного фонду Волині, виділяємо клас антропогенних ландшафтів забудовані землі, тобто, власне, селитебні ландшафти. В результаті аналізу картосхем різних часових періодів для території с. Згорани, яке знаходиться в межах КД-1, досліджено зміну не тільки площі селитебного ландшафту, але й зміну його рисунка протягом століття. З метою оцінки сучасного стану використання територій населених пунктів визначено частку земель селитебно-житлової забудови в загальній площі забудованих територій. За результатами дослідження складено картосхеми, діаграми. Обґрунтовано основні напрями геоекологічної реабілітації селитебних ландшафтів для потреб регіонального розвитку.

The paper displays the results of the assessment of special aspects of the current condition of the built-up land use for the territory of Polissia in Volyn region. As follows from the analysis of Volyn’s land resource structure, we have marked out a class of anthropogenic landscapes as built-up lands, so, basically, lands intended for building. Lands intended for building and built-up landscapes are some of the most complex and intensively rising anthropogenic landscapes in the structure of the land use. As a result of processing theoretically methodological fundamentals of anthropogenic landscape study, and the assessment of the condition of lands within the research area, a functional typology of lands intended for building has been established. The analysis of the current condition of lands is represented at the administrative micro-level (village, town, city councils). To define built-up lands of Polissia, we have processed the information within the territory of Liubomylskyi and Kamin-Kashyrskyi districts where the key localities were marked. The part of built-up lands within the land structure was determined. In this case, lands intended for building and the development of transportation, recreational and residential system, are predominant. As follows from the analysis of map charts illustrating the territory of village Zhorany (which is within the key locality 1) in different periods of time, not only the change of the land intended for building was analyzed, but the change of its pattern during the century. In order to assess the current condition of usage of inhabited localities, the part of the land intended for building and residence was determined within the total area of built-up areas. Based on the research findings, map charts and diagrams are generated. The major lines of geo-ecological rehabilitation of lands allotted for settlement for regional development needs were established.
The geographical assessment of the current condition of the built-up land use in the territory of Polissia (Volyn region)
Keywords: built-up lands; laid use; lands intended for building; забудовані землі; землекористування; рисунок ландшафту; селитебно-забудовані землі; селитебний ландшафт; цифрова векторна модель